Nursing strategies to promote patient safety in the performance of indwelling urinary catheterization in the emergency department: An integrative literature review (Research, Society and Development, 2025)
Introduction: Indwelling urinary catheterization is widely used in urgent and emergency care, but when performed incorrectly, it may lead to complications such as catheter-associated urinary tract infections. In this context, nursing plays a central role in patient safety, acting both in the aseptic technique and in the implementation of protocols and preventive measures. Objective: To identify and analyze nursing strategies aimed at patient safety during the performance of indwelling urinary catheterization in emergency settings. Methodology: This is an integrative literature review, in which 23 articles were analyzed, of which 10 met the inclusion criteria, resulting in 5 studies used for the final discussion, according to the adapted PRISMA flowchart. Results: It was evidenced that the adoption of care protocols, strict hand hygiene, the use of aseptic technique, the appropriate choice of catheter, correct fixation, reduced length of catheterization, and continuous nursing education are fundamental strategies to minimize risks and prevent complications. It was also observed that the standardization of care and the strengthening of a patient safety culture significantly contribute to the quality of care. Conclusion: Nursing practice is decisive for patient safety during indwelling urinary catheterization, making continuous training and adherence to best practice protocols essential, especially in the emergency context, where the agility of care should not compromise the quality of the procedure.